1992
DOI: 10.2134/agronj1992.00021962008400060004x
|View full text |Cite
|
Sign up to set email alerts
|

Mepiquat Chloride and Irrigation versus Cotton Growth and Development

Abstract: Cotton (Gossypium hirsutum L.) produces excessive vegetative growth when grown under optimum water and nutrient conditions. The plant growth regulator Mepiquat Chloride (MC); 1,l‐dimethyl piperidinium chloride reduces vegetative growth and can promote early maturity. Its effect on yield has been inconsistent, with some researchers showing an increase while others have indicated a decrease. This variation in yield has often been attributed to environmental factors and variations in water and fertilizer inputs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0
13

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 9 publications
5
22
0
13
Order By: Relevance
“…They have similar modes of action and effects, which is to inhibit gibberellic acid biosynthesis and thus reduce cellular elongation, resulting in lower growth rate (Lamas, 2001). The technique also increases 100-seed weight and cotton boll size, enhancing early fruit opening, harvest efficiency and production of high quality fibers (Cruz et al, 1982;Reddy et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…They have similar modes of action and effects, which is to inhibit gibberellic acid biosynthesis and thus reduce cellular elongation, resulting in lower growth rate (Lamas, 2001). The technique also increases 100-seed weight and cotton boll size, enhancing early fruit opening, harvest efficiency and production of high quality fibers (Cruz et al, 1982;Reddy et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…MC regulating plant growth has been extensively researched and well documented (York, 1983a;1983b). It was reported that MC tends to be shorter and more compact than untreated plants (Jung et al, 1975;Willard et al, 1976;Stuart et al, 1984;Kerby, 1985;Hodges et al, 1991;Reddy et al, 1992). Number of branch per plant in the MC and TE was increased by high concentration, which is attributed to the significant increase in seed yield.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the good population type and canopy structure for dwarf plants, smaller leaves and bigger bolls could be achieved by mepiquat chloride application. Mepiquat chloride and trinexapac-ethyl tend to be shorter and more compact than untreated plants (Jung et al, 1975;Willard et al, 1976;Stuart et al, 1984, Kerby 1985Hodges et al, 1991;Reddy et al, 1992). Hence, we proposed these studies with the objective to demonstrate the effect of MC and TE on oil composition, seed yield, endogenous gibberellins content in flax plant.…”
Section: Introductionmentioning
confidence: 99%
“…Mepiquat chloride, a gibberellic acid synthesis inhibitor, is one of the most widely used growth regulators in cotton. The impact of mepiquat chloride on stem elongation and plant height are temperature dependent (Reddy et al 1992) and, at high temperatures, higher PGR rates are needed to control plant growth (Rosolem et al 2013). The PGR 1.…”
Section: Abstract Resumomentioning
confidence: 99%